1998
DOI: 10.1093/jn/128.12.2446
|View full text |Cite
|
Sign up to set email alerts
|

Absorption of Nutrients Is Only Slightly Reduced by Supplementing Enteral Formulas with Viscous Fiber in Miniature Pigs

Abstract: Viscous polysaccharides reduce intestinal absorption of glucose and diminish postprandial hyperglycemia. However, it is unknown whether viscous fiber also inhibits absorption of nutrients under conditions of enteric feeding. Therefore, we measured the absorption rates of nutrients in miniature pigs by perfusing a 150-cm length of jejunum with 8.37 kJ/min of the three following enteral diets: an isoosmotic oligomeric diet (1670 kJ/L), a hyperosmotic oligomeric diet and an isoosmotic polymeric diet (both 3350 kJ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 27 publications
2
8
0
Order By: Relevance
“…The model predictions in terms of the gastric-emptying half-time, flow rates of absorption, and net absorption from the different intestinal lumen compartments are strikingly in line with current knowledge of gastrointestinal kinetics (3,8,21,29,60), as summarized in Table 4. For instance, ϳ80% of dietary N absorption was predicted to occur in the upper part of the gastrointestinal tract, in line with the idea that dietary N is principally absorbed in the proximal part of the small intestine (28,29,60).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The model predictions in terms of the gastric-emptying half-time, flow rates of absorption, and net absorption from the different intestinal lumen compartments are strikingly in line with current knowledge of gastrointestinal kinetics (3,8,21,29,60), as summarized in Table 4. For instance, ϳ80% of dietary N absorption was predicted to occur in the upper part of the gastrointestinal tract, in line with the idea that dietary N is principally absorbed in the proximal part of the small intestine (28,29,60).…”
Section: Discussionsupporting
confidence: 79%
“…In humans, a compartmental analysis such as the one accomplished here would enable assessment of the d Half-time of gastric emptying of proteins after a mixed-protein meal of 1,840 kJ in humans (with a ratio of nutrients close to that of our meal: 51% carbohydrate; 15% protein; 35% fat) (8). e Mean absorption rate of protein along a 150-cm-long segment of jejunum after infusion into the jejunal segment of an enteral diet (50% carbohydrate; 20% protein; 30% fat) at a rate of 68 mg protein/min in miniature pigs (21).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, other studies have shown that increasing the viscosity of diets for grower pigs results in corresponding increases in the viscosity of the small intestinal contents for several hours after feeding (Cherbut et al 1990;Ellis et al 1995;Ehrlein & Haas-Deppe, 1998;Ehrlein & Stockmann, 1998).…”
Section: Discussionmentioning
confidence: 95%
“…A second dietary approach to stimulate small intestinal hyperosmolarity could be to enhance levels of macronutrient polymers (i.e., proteins and carbohydrates), which during digestion produce many transiently osmotically active oligo-and monomers (23,65). One observation supporting this concept is that weight loss after a low-fat, high-carbohydrate diet is not associated with the usually observed compensatory rise in ghrelin (88).…”
Section: Discussionmentioning
confidence: 99%